PERANAN AKAL DAN WAHYU DALAM PEMIKIRAN ISLAM - siar, Siar Nimah; Andi Aderus; Barsihannor (Program Studi Ilmu Tasawuf IAI Pangeran Diponegoro Nganjuk, Jawa Timur, 2024)
This article discusses how the reason and the revelation play a role in the treasures of Islamic thought. The type of research used is library research by collecting data from the library, both primary and secondary data. Then the data that has been collected is analyzed using analytical descriptive data analysis to present a complete conclusion. This research produces at least three main points, namely: first, the reason has a high value in the Qur'an, including the command for humans to think. Second, from a theological perspective, the reason and revelation are given their own portions, the Mu'tazilah with a larger portion of reason and the Asy'ariyah with a smaller portion of reason dissolving revelation. Third, from a philosopher's perspective, the eason and revelation are two things that are compatible in the view of Ibn Rushd and al-Kindi.